Use of Balanced Score card to measure the strategic performance of Laghouat Mills - Taibaoui, Amina; Boderbala, Sarah Hadda (Dirassat Journal Economic Issue, 2019)
The objective of this study is to present a model for the implementation of the Balanced ScoreCard to measure the strategic performance at Laghouat Mills Company during the period 2014-2017. In the theoretical aspect, we discussed the concept of measuring strategic performance and the most important measurement models, and focused on Balanced Score Card model, On the practical side, the perspectives of the Balanced Scorecard have been applied in the process of evaluation and measurement of strategic performance. The study has reached the importance of this card in measuring of financial and non-financial performance as well as in the short and long term, and that the company attaches great importance to the customers, learning and growth perspectives, which helps it to achieve their strategic objectives and ensure excellence and continuity.